Compactação de Cambissolo e Neossolos Causada Pela Colheita de Madeira com Feller-buncher e Skidder - Sampietro, Jean Alberto (2010)
The compaction caused by traffic of timber harvesting machines is an important factor because of the possibility of changing the properties of the soil, affecting plant growth, and thus causing losses in forest productivity. The aim of this study was to evaluate the compaction caused by traffic of timber harvesting machines in different soils subjected to different moistures and traffic intensities in stands of Pinus taeda L., contributing with information to the planning of operations, forestry sustainability, increased productivity and reduction of costs. The studies were conducted in the operational areas of the company Battistella Florestal, located in the Northern Part of the State of Santa Catarina. To analyze the influence of moisture content in compaction, data were obtained at different times, during the dry and rainy seasons, accommodating different soil moisture contents divided into classes, and compared the difference between the situation without traffic and after machines traffic. To reveal the effects of the traffic intensity in compaction, sample plots were established according to the simulation of different traffic conditions. To evaluate the compaction, bulk density, total porosity and soil resistance to penetration were determined. The main results were: the elevation of soil moisture content resulted in major changes of the studies properties, demonstrating that the traffic of the machines in wet conditions cause greater compaction; most part of the compaction at evaluated soils has resulted of the first pass of the forest harvesting machines; the traffic of machinery caused changes in soil up to 80 cm depth and 100 cm away from the line of the wheelsets; the evaluated soils behaved differently to the imposed conditions. In general, the needed of measures to reduce soil compaction was confirmed, according to the moisture content, traffic intensity and soil type. The monitoring of precipitation and concentration of traffic into predetermined carriers, can contribute to reduce the extent of soil compaction effects, reducing the environment impacts and future forest rotations.